Assessing the role played by biofilms on adenoidal surface in a pediatric population - Rodrigues, João (2019)
Adenoids are a mass of lymphatic tissue located within the nasopharynge. This work aims assessing the relationship between the formation of bacterial biofilms on the adenoid surface and the incidence of infections in the pediatric age.